Jejak Kebangkitan Pers Kota Banjarmasin Pasca 1998 - Prayudha Aditya; Syaharuddin Syaharuddin; Rochgiyanti Rochgiyanti; Fitri Mardiani; Melisa Prawitasari (Pendidikan IPS FKIP ULM, 2022)
The press is one of the institutions in society that bridges information between the public and the government through the mass media. In the life of a democratic community, nation, and state, freedom to express thoughts and opinions according to one's conscience and the right to obtain information must be guaranteed because these are the most basic human rights. In reality, the implementation of press freedom in the Reformation Era still faces many obstacles. Considering the political direction previously during the New Order era, which tended to be personal, very strong, and authoritative, in the following period, there were major changes for the press in Indonesia, including in Banjarmasin. This study explores how is the role of PWI in unifying forum for journalists nationall and creating a major contribution to maintaining the pillars of democracy in the realization of the post-1998 press in Banjarmasin City.Keywords: Press, Banjarmasin City, Post-1998